Functional blended yarn and preparation method thereof
The nanoscale chemical fibers are attached to the natural fiber membrane through electrostatic coating technology to form a wettable and riveted second fiber membrane, which solves the problems of poor fiber functionality and uneven dyeing in the prior art, achieves efficient antibacterial, antibacterial and mite-resistant properties, and improves the washing resistance and durability of the yarn.
Patent Information
- Application Number
- CN202411917150.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-03-28
AI Technical Summary
The existing electrospinning technology is difficult to effectively embed chemical fibers into natural fibers, resulting in poor antibacterial, antibacterial and mite-resistant properties of functional blended yarns, uneven dyeing of fibers and poor washing resistance.
Using electrostatic coating technology, nanoscale functional chemical fibers are attached to the natural fiber membrane in the form of an electrocoating liquid to form a second fiber membrane that mixes natural fibers and chemical fibers. Through the action of high-voltage electric field, the polymer in the electrocoating liquid forms wettable riveting on natural fibers, enhancing the functionality of the fibers.
The antibacterial, antibacterial and mite-resistant properties of the blended yarn are significantly improved, so that it can maintain good functionality after washing and rubbing, and the fibers are dyed evenly and durable.
Smart Images

Figure CN119710999A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electrostatic coating, and in particular to a functional blended yarn and a preparation method thereof. Background Art
[0002] Functional blended yarn is a type of yarn made by mixing two or more fibers with different characteristics to obtain specific physical, chemical or mechanical properties. These yarns combine the excellent properties of different fibers, such as improved strength, elasticity, moisture absorption, antibacterial or UV protection, to meet specific application needs or performance requirements. Functional blended yarns are widely used in clothing, home textiles and technical textiles to enhance the comfort, durability and functionality of products by optimizing fiber combinations.
[0003] At present, there are several traditional methods for using yarns and fabrics made of natural fibers such as cotton, linen, and wool to have antibacterial, antibacterial, and / or anti-mite functions:
[0004] (1) blending micron-sized chemical fibers containing antibacterial, antibacterial and / or anti-mite agents with natural fibers to form synthetic yarns, so that the synthetic yarns have antibacterial, antibacterial and / or anti-mite effects;
[0005] (2) adding powder solids of antibacterial, antimicrobial and / or anti-mite agents during the spinning process of natural fibers, and allowing these powders to be mixed into the formed yarn, so that the synthetic yarn has antibacterial, antimicrobial and / or anti-mite effects;
[0006] (3) After the yarn is woven into fabric, the fabric is immersed in a solution of an antibacterial, antimicrobial and / or anti-mite agent, and then subjected to a series of treatments to fix the agent immersed in the fabric as much as possible.
[0007] These traditional methods have disadvantages. For example, in traditional textiles, a yarn contains micron-sized fibers of different materials. Because fibers of different materials have different coloring abilities in the same pigment / dye, the fibers of the yarn are not dyed uniformly. Another example is that the yarn or fabric produced by traditional methods is often not washable, and the antibacterial, antibacterial and / or anti-mite effects cannot be maintained after multiple washings.
[0008] Although the electrospinning process in the prior art can attach functional chemical fibers to natural fibers, it still has a significant defect: the products formed by spinning can only be solidified into fibers. For natural fibers, the fibers solidified by electrospinning are difficult to enter the natural fibers, and the wettability and coating effects on the natural fibers are poor, resulting in poor riveting effect between chemical fibers and natural fibers.
[0009] For example, CN111636110A discloses a method for preparing antibacterial electrospun fibers based on polyionic liquids, comprising the following steps: (a) using acrylonitrile and 4-vinylpyridine as monomers to copolymerize to obtain a copolymer; (b) reacting the copolymer with Carry out grafting reaction to obtain polyionic liquid; (c) dissolve the polyionic liquid in DMF to obtain electrospinning solution of polymer solution, connect the electrospinning solution to the electrospinning machine, and prepare antibacterial, antibacterial and / or anti-mite electrospun fibers. This technical solution is to use a mixed polymer solution for spinning, so that the proportion of natural fibers is reduced. Obviously, for natural fiber materials, electrospinning cannot directly infiltrate chemical fibers into natural fibers, and therefore cannot provide blended yarns with a high proportion of natural fibers and good functionality.
[0010] Therefore, how to improve the preparation method of mixed yarn and the structure of mixed yarn so that the functionality of mixed yarn (such as antibacterial, antibacterial and / or anti-mite properties) is durable is a technical problem that needs to be solved.
[0011] In addition, on the one hand, there are differences in understanding among those skilled in the art; on the other hand, the applicant studied a large number of documents and patents when making the present invention, but due to space limitations, not all details and contents are listed in detail. However, this does not mean that the present invention does not have the characteristics of these prior arts. On the contrary, the present invention already has all the characteristics of the prior art, and the applicant reserves the right to add relevant prior art to the background technology. Summary of the invention
[0012] These traditional electrospinning methods have many disadvantages. For example, in traditional textiles, there are fibers of different materials in a yarn. Because the coloring ability of fibers of different materials in the same pigment / dye is different, the fibers of this yarn are not evenly dyed. For another example, the yarn or cloth made in the traditional way is often not washable, and the antibacterial and anti-mite effects cannot be maintained after multiple washings. For another example, the antibacterial agent in the fiber is unevenly distributed or the antibacterial agent is difficult to contact with bacteria, resulting in reduced antibacterial properties, and when used in the field of air filtration, it rubs against particles in the air, thereby reducing the antibacterial effect. How to improve the preparation method of mixed spinning and the structure of mixed spinning so that the functionality of the mixed spinning (such as antibacterial, antibacterial and / or anti-mite properties) is durable is a technical problem that the present invention needs to solve.
[0013] In view of the deficiencies in the prior art, the present invention provides a functional blended yarn from a first aspect, wherein the fibers of the blended yarn include natural fibers and nanoscale functional chemical fibers, wherein an electrocoating liquid related to the chemical fibers is attached to a first fiber membrane formed by natural fibers in an electrostatic coating manner to form a second fiber membrane of mixed natural fibers and chemical fibers, and during the electrostatic coating process, the high molecular polymer in the electrocoating liquid forms a wettability fixation on the natural fibers, so that the high molecular polymer is embedded in the natural fibers to enhance the functionality of the natural fibers; the blended yarn is spun from the second fiber membrane.
[0014] The present invention uses electrostatic coating to impregnate and coat natural fibers with long fibers, short fibers, short rods and / or particles. This coating can not only enhance the aggregation of natural fibers, but also embed more functional substances into natural fibers to enhance the functionality of natural fibers.
[0015] According to a preferred embodiment, the electrostatic coating method includes: the electrocoating liquid forms nanoscale fibers, short rods or particles under the action of a high voltage electric field and is coated on the surface of the first fiber membrane. By forming nanoscale fibers, short rods or particles by electrostatic coating, functional layers with different riveting degrees can be formed on the surface of the first fiber membrane. This fiber membrane not only provides a larger surface area for the attachment of functional substances, but also increases the mechanical strength and weather resistance of the fiber membrane. The formation of the second fiber membrane improves the overall functionality of the fiber membrane, such as enhancing antibacterial properties, ultraviolet protection, and moisture absorption and perspiration performance.
[0016] According to a preferred embodiment, when the electro-coating liquid is formed by mixing at least three substances, the mixing method of the electro-coating liquid includes: the electro-coating liquid provided by at least two liquid holding boxes is mixed during the liquid supply process; the electro-coating liquid provided by at least two liquid holding boxes is instantly contacted and sprayed out when the liquid is discharged; the electro-coating liquid provided by at least two liquid holding boxes forms a core-sheath structure in which the sheath liquid surrounds the core liquid when spraying.
[0017] Through different mixing methods, the electrocoating solution can be precisely formulated to form a multifunctional coating. The formation of the electrocoating solution with mixing, instant contact spraying, and core-sheath structure can achieve complex chemical and physical functions on the fiber surface. In particular, the core-sheath structure can achieve the integration of multi-level functions, further enhancing the durability and functionality of the fiber.
[0018] According to a preferred embodiment, the electrostatic coating process of the second fiber membrane includes: when the voltage of the high voltage electric field is unstable, the electro-coating jet of the electro-coating liquid is uneven and forms a bead string structure, and the short rods in the bead string structure wrap the first fiber membrane in a liquid state and rivet in the first fiber membrane. The short rod structure can provide effective mechanical connection and chemical bonding, significantly improve the tensile strength and elasticity of the fiber membrane, and promote the stable embedding of functional substances, thereby enhancing the overall performance of natural fibers.
[0019] According to a preferred embodiment, the mass content of natural fiber materials in the blended yarn is not less than 90%; or, the proportion of nanoscale materials in nanoscale functional chemical fibers is not less than 90%. When the content of natural fiber materials is not less than 90%, the wetting effect of electrostatic coating can significantly improve the overall performance of natural fibers, such as improving touch and wearability. When the proportion of nanomaterials in nanoscale functional chemical fibers is not less than 90%, the functional characteristics of the yarn (such as conductivity, optical properties, mechanical properties, and macroscopic chemical properties) can be better maintained. In either case, the electrostatic coating technology ensures that the functional substances play a comprehensive and continuous role through the uniform distribution and long-term adhesion of nanomaterials while maintaining a high content of natural fibers, thereby optimizing the performance of the yarn in high-performance applications.
[0020] The present invention provides a method for preparing a functional blended yarn from a second aspect, the method comprising: making a natural fiber into a first fiber membrane; attaching an electrocoating liquid related to chemical fibers to the first fiber membrane by electrostatic coating to form a second fiber membrane of mixed natural fibers and chemical fibers, during the electrostatic coating process, the polymer in the electrocoating liquid forms an impregnation fixation on the natural fibers, so that the polymer is embedded in the natural fibers to enhance the functionality of the natural fibers and maintain the functionality for a long time; making the second fiber membrane into a blended yarn. The present invention attaches a polymer to a natural fiber membrane in the form of an electrocoating liquid by an electrostatic coating method to form a second fiber membrane of mixed natural fibers and chemical fibers. The impregnation fixation of the polymer can enhance the functionality of the natural fibers, such as improving their toughness, wear resistance, antibacterial, antibacterial and anti-mite properties. This process significantly improves the functionality and structural properties of the fibers, and the blended yarn produced is more superior in performance.
[0021] According to a preferred embodiment, the method further comprises: adjusting the potential difference, voltage and the changing rule of the high-voltage electric field, so that the electro-coating liquid forms nano-scale fibers, short rods or particles under the action of the high-voltage electric field and is coated on the surface of the first fiber membrane. By adjusting the potential difference and voltage of the high-voltage electric field and the changing rule thereof, the electro-coating liquid can form nano-scale fibers, short rods or particles on the surface of the first fiber membrane. These nanostructures greatly increase the surface area of the fiber membrane, thereby improving the loading capacity and effectiveness of its functional materials.
[0022] According to a preferred embodiment, the method further includes: in the case where the electrocoating liquid is formed by mixing at least three substances, the mixing method of the electrocoating liquid includes: the electrocoating liquid provided by at least two liquid storage boxes is mixed during the liquid supply process; the electrocoating liquid provided by at least two liquid storage boxes is immediately contacted and sprayed when the liquid is discharged; the electrocoating liquid provided by at least two liquid storage boxes forms a core-sheath structure in which the sheath liquid surrounds the core liquid when spraying. The use of a variety of liquid electrocoating liquid mixing methods such as mixing, immediate contact spraying and core-sheath structure can make the first fiber membrane become a second fiber membrane with a variety of different functionalities. This method ensures the enhancement of the functionality of natural fibers, such as the integration of antibacterial, antibacterial and anti-mite functions, making natural fibers more diverse in application and functionally complex.
[0023] According to a preferred embodiment, the method further comprises: adjusting the voltage of the high-voltage electric field to an unstable state, so that the electrocoating jet of the electrocoating liquid is uneven and forms a beaded structure, and the short rods in the beaded structure wrap the first fiber membrane in a liquid state and rivet in the first fiber membrane. By adjusting the high-voltage electric field to an unstable state, the formed beaded structure provides a unique short rod morphology on the first fiber membrane. These short rods are wrapped in the first fiber membrane in a liquid state and riveted, which improves the mechanical properties and overall stability of the natural fiber. This structure can effectively embed functional materials, improve the fatigue resistance and durability of natural fibers, and especially improve the antibacterial, antibacterial and / or anti-mite properties.
[0024] According to a preferred embodiment, the method further includes: adjusting the electric field strength of the high voltage electric field to an unstable state, so that the electrocoating jet of the electrocoating liquid is uneven and forms droplets, and the droplets are deposited on the surface and / or inside the first fiber membrane, thereby solidifying into particles on the surface and / or inside the first fiber membrane to achieve riveting. By utilizing the unstable electric field strength, the droplets formed by the electrocoating liquid can be deposited on the surface or inside the first fiber membrane and solidify into particles. This process achieves uniform distribution and riveting of functional materials on the surface or inside of natural fibers, significantly improving the functional properties of the fibers such as antibacterial, fireproof and enhanced strength. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 It is a simplified schematic diagram of the module connection relationship of the electrostatic coating device provided by the present invention;
[0026] Figure 2 is a schematic structural diagram of the electrostatic coating device provided by the present invention in a side view;
[0027] Figure 3 It is a schematic structural diagram of the electrostatic coating device provided by the present invention when viewed from an upward angle;
[0028] Figure 4is a schematic structural diagram of the nozzle provided by the present invention when it is in a first form;
[0029] Figure 5 is a schematic structural diagram of the nozzle provided by the present invention when it is in the second state;
[0030] Figure 6 is a schematic structural diagram of the nozzle provided by the present invention when it is in the third state;
[0031] Figure 7 It is a simplified structural schematic diagram of the electrostatic coating device provided by the present invention.
[0032] Reference numerals list
[0033] 100: electrostatic coating device; 110: nozzle; 120: receiving end; 130: electric field control component; 131: transmitting electrode; 132: receiving electrode; 140: liquid supply component; 141: first liquid infusion pipeline; 142: second liquid infusion pipeline; 143: third liquid infusion pipeline; 144: liquid storage box; 150: processing component; 160: detection component; 200: transmission device; 300: processing device; 400: collecting device; 500: substrate; 600: fiber combing equipment. DETAILED DESCRIPTION
[0034] The following is a detailed description with reference to the accompanying drawings.
[0035] The present invention explains some of the noun terms.
[0036] Electrospinning: The process of stretching a polymer or melt into continuous fine fibers through a high voltage electric field. The process involves extruding a polymer fluid into an electric field, where the fluid is stretched into extremely fine fibers and solidified. Electrospinning can produce fibers with nanometer diameters that have high specific surface areas and unique physical properties.
[0037] Electrocoating (Electrocoating for short): Different from electrospinning, it refers to the process of processing polymer fluids through high-voltage electric fields to form and produce products in various forms. The products formed are not limited to fibers, but also include short rods and droplets.
[0038] Electrocoating liquid: It is a liquid material specially designed for electrostatic coating (electrocoating for short) process. It can exist in the form of solution, sol, suspension or emulsion. During the electrostatic coating process, the polymer fluid in the electrocoating liquid is attracted to the surface of natural fibers with opposite charges under the action of a high-voltage electric field, and is uniformly deposited to form a chemical fiber coating. The chemical fibers in this process can not only generate fibrous structures, but also form chemical fiber materials in various forms such as short rods and droplets, making the riveting of chemical fibers and natural fibers more secure. In addition, compared with traditional electrostatic spraying methods, the electrocoating process can also significantly reduce the emission of volatile organic compounds (VOCs), which is more environmentally friendly.
[0039] Beaded structure: When the voltage of the electric field is unstable, the electrocoating jet is uneven, thus forming a beaded structure in which droplets and fibers alternate in the fiber, similar to the "beaded" shape in which beads and thin wires alternate. In the beaded structure, the droplets are more difficult to solidify in the same time, so there is enough time to wrap the natural fiber and rivet in the natural fiber. This riveting is more conducive to the combination of high molecular polymer materials (chemical fiber materials) and natural fiber materials, and significantly reduces the possibility of separation of high molecular polymer materials from natural fibers under the action of macroscopic external forces.
[0040] Short rods: In a beaded structure, short rods are those relatively short and thick sections. These short rods are usually more difficult to cure or dry quickly than the thinner sections due to their larger diameter. Because the short rod sections cure more slowly, they remain in a liquid state longer. This extended cure time allows the polymer solution in the short rod sections to interact more with the natural fibers, effectively wrapping around them and "snapping" or fixing them to the natural fibers.
[0041] Particles: When the electrocoating liquid is ejected from the nozzle 110, if the surface tension, viscosity or voltage conditions of the droplets are not suitable for drawing, continuous fibers may not be formed. In this case, the liquid may break into small parts, which form granular structures instead of long and thin fibers during the solidification process. At the nanoscale, the diameter of these particles is usually between tens and hundreds of nanometers, depending on the characteristics of the solution and the process parameters.
[0042] Example 1
[0043] This embodiment provides a functional blended yarn and a preparation method thereof.
[0044] The present embodiment provides a functional blended yarn, and the nanoscale fibers of the blended yarn include natural fibers and nanoscale functional chemical fibers. The chemical fibers can be high molecular polymers. Natural fibers refer to fiber materials obtained directly from nature, mainly from plants, animals or mineral resources. Plant fibers such as cotton, hemp and flax are mainly composed of cellulose; animal fibers such as wool and silk have protein as the main component; mineral fibers such as asbestos are composed of minerals. In the present invention, chemical fibers are fibrous substances formed by artificially synthesized electrocoating liquid under the action of an electric field. On the surface or inside of the natural fibers of the present invention, the chemical fibers are not limited to filaments, but can also be short rods or granules.
[0045] For electrostatic coating technology, factors that lead to different spinning amounts include:
[0046] (1) Voltage: The voltage directly affects the strength of the electric field during the spinning process. A higher voltage can enhance the distribution of charges in the electrocoating solution, thereby increasing the electrocoating rate and fiber uniformity. However, too high a voltage may lead to unstable jetting and fiber breakage.
[0047] (2) Drum speed: The drum speed determines the fiber drawing speed and the final fiber diameter. A higher speed can draw finer fibers, but it also needs to be controlled within an appropriate range to avoid fiber breakage or unevenness during the formation process.
[0048] (3) Performance properties of the electrocoating liquid: The properties of the electrocoating liquid such as viscosity, conductivity and surface tension have an important influence on the electrocoating process. Too high viscosity may lead to difficulty in fiber formation, while too low viscosity may lead to fiber instability. Conductivity and surface tension will also affect the conduction of charge and the quality of fiber formation.
[0049] (4) Environmental variables: Factors such as ambient temperature, humidity, and air flow can also affect the spinning volume. Changes in temperature and humidity may affect the evaporation rate of the solution and the drying process of the fiber, while air flow may affect the fiber path and the final fiber arrangement.
[0050] The parameters have a significant impact on the spinning amount, which is reflected in the following aspects:
[0051] First, if the spinning amount is insufficient, the fiber layer formed may be too thin to fully realize the expected functionality of the yarn, such as antibacterial, antimicrobial, anti-mite, deodorizing and anti-mildew properties. This is because the functional substances may not be evenly distributed or reach a sufficient concentration, thus reducing the overall performance of the yarn.
[0052] On the contrary, if the spinning amount is too large, the fiber layer may be too thick, resulting in too high a proportion of chemical fibers, which in turn leads to problems such as color difference and tactile changes in dyeing. This is because the coloring mechanism of dyes in the printing and dyeing process of natural fibers and chemical fibers is different, resulting in uneven color. In addition, excessive spinning amount may cause changes in fiber structure, affecting the tactile and mechanical properties of the fiber.
[0053] Therefore, reasonable control of the spinning amount can not only ensure the functionality of the yarn, but also improve its appearance quality. By adjusting the parameters in the electrostatic coating process such as the electric field strength and spinning time, the electrostatic coating process can be finely controlled to produce high-quality products that meet specific application requirements.
[0054] This embodiment adjusts the raw materials and fiber diameters, matches the natural fibers with appropriate chemical fiber membranes, and uses electrostatic coating and electric field fluctuation control to improve the combination of chemical fibers and natural fibers and reduce the possibility of separation between the two.
[0055] The preparation method of the functional blended yarn of this embodiment is as follows.
[0056] S110: Forming a first fiber membrane from natural fibers.
[0057] In the process of making the natural fiber material into the first fiber membrane, it is first necessary to select a suitable natural fiber material and dissolve it in a suitable solvent to make a uniform spinning solution. For example, the solution is stretched into ultrafine fibers by high voltage. The first fiber membrane is a nanoscale fiber membrane. The surface shape of the first fiber membrane is not limited and can be an irregular shape.
[0058] Preferably, the first fiber membrane is also formed by a carding process.
[0059] The main principle of carding is to comb fiber raw materials such as cotton or wool to form a uniform fiber web or yarn, i.e., the first fiber film. First, through the opening process, the fiber mass is loosened to remove impurities and facilitate dispersion. Then, the fiber is combed through the fiber combing device 600. The fiber combing device 600 is provided with a series of rollers and working rollers with needle teeth, so that the entangled fibers are straightened and form a basically parallel fiber layer, while removing shorter fibers and residual impurities to ensure quality. Subsequently, the fibers gradually form a uniform fiber web, and in the final stage are gently stretched and wound into strips, ready to enter the spinning process. Through these steps, carding greatly improves the uniformity and quality of the fibers, providing a high-quality raw material basis for subsequent processing.
[0060] S120: attaching the electrocoating liquid related to the chemical fiber to the first fiber membrane by electrostatic coating to form a second fiber membrane of mixed natural fiber and chemical fiber. During the electrostatic coating process, the high molecular polymer in the electrocoating liquid forms a wettability fixation on the natural fiber, so that the high molecular polymer is embedded in the natural fiber to enhance the functionality of the natural fiber.
[0061] Specifically, the electrocoating liquid containing chemical fibers is ejected from the nozzle 110 under the action of the electric field and forms an electrocoating jet. The electrocoating jet is coated on the surface of the first fiber membrane in the form of nanofibers, short rods or particles. Preferably, the curing time of the short rods or particles is long, so during the curing process, a portion of the electrocoating liquid is absorbed by the first fiber membrane into its interior. In this way, the short rods and particles carry out an infiltration coating on the natural fibers, covering more or even all of the surface of the first fiber membrane. After the short rods or particles are cured, the electrocoating liquid on the surface of the first fiber membrane and the electrocoating liquid absorbed inside it are more deeply "inserted" into the first fiber membrane, achieving riveting, so that the connection between the chemical fiber and the natural fiber is tighter and difficult to separate. In this way, the second fiber membrane formed by electrostatic coating retains the characteristics of natural fibers and has the functionality of chemical fibers.
[0062] S121: adjusting the potential difference, voltage and variation rule of the high voltage electric field so that the electro-coating liquid forms nano-scale fibers, short rods or particles under the action of the high voltage electric field and is coated on the surface of the first fiber membrane.
[0063] The electric field force acts on the droplets in the electrocoating liquid to form a "Taylor cone". Once the electric field force exceeds the surface tension of the liquid, the electrocoating jet is ejected and stretched and thinned in the air. As the solvent evaporates quickly, a nanostructure is generated. By controlling the potential difference and voltage, the morphology and structural size of the electrocoating jet can be affected. Higher voltage is generally conducive to the formation of finer fibers.
[0064] When the voltage of the electric field is turned down, the behavior and structure of the electrocoating fluid are different. At lower voltages, the electric field force is not strong enough to stretch the electrocoating jet significantly, resulting in the droplets only partially stretching under the action of the electric field or not forming stable fibers, making it easier to form short rods and particles. When the voltage is low, the speed and stretching force of the electrocoating jet decrease, and the droplets in the solution tend to maintain a larger volume and retract under the action of surface tension, resulting in the formation of shorter fibers or direct condensation into particles. In addition, the electric field strength at lower voltages may not be sufficient to maintain a stable Taylor cone, which causes the droplets to break up into discrete particles.
[0065] In contrast to the high and stable voltage regulation method of electrospinning, the electrostatic coating of the present invention is to reversely lower the voltage and make it unstable, so that short rods or particles appear in the electrocoating liquid, so that the electrocoating liquid can cover and wet the natural fiber on the surface of the first fiber membrane in the form of short rods or particles.
[0066] Preferably, the present invention can also adjust the potential difference and voltage of the high voltage electric field and make it have a certain change rule, so that the electro-coating liquid forms short rods or particles in a specified size range under the action of the electric field.
[0067] Preferably, the voltage of the high voltage electric field is adjusted to an unstable state, so that the electrocoating jet of the electrocoating liquid is uneven and forms a bead string structure. The short rods in the bead string structure wrap the first fiber membrane in liquid state and are riveted in the first fiber membrane.
[0068] Preferably, the shape of the protruding liquid beads in the beaded structure can be a regular shape (such as a nearly circular structure) or an irregular arbitrary shape.
[0069] By adjusting the high voltage electric field to an unstable state, the beaded structure formed provides a unique short rod morphology on the first fiber membrane. These short rods are wrapped in a liquid state on the first fiber membrane and riveted, which improves the mechanical properties and overall stability of the natural fiber. This structure can effectively embed functional materials, improve the fatigue resistance and durability of natural fibers, and especially improve the antibacterial, antibacterial and / or anti-mite properties.
[0070] Preferably, the electric field strength of the high-voltage electric field is adjusted to an unstable state, so that the electrocoating jet of the electrocoating liquid is uneven and forms droplets. The droplets are deposited on the surface and / or inside the first fiber membrane, thereby solidifying into particles on the surface and / or inside the first fiber membrane to achieve riveting. By utilizing the unstable electric field strength, the droplets formed by the electrocoating liquid can be deposited on the surface or inside the first fiber membrane and solidify into particles. This process achieves uniform distribution and riveting of functional materials on the surface or inside of natural fibers, significantly improving the functional properties of the fibers such as antibacterial, fireproof and enhanced strength.
[0071] For example, periodic voltage regulation is performed and the electrocoating fluid is formed into short rods.
[0072] The electric field adopts a periodically changing voltage mode. By adjusting the voltage to increase and decrease periodically, the electrocoating jet can be made to present a periodic stretching and contraction state in the electric field. When the voltage is high, the electrocoating jet is subjected to a greater stretching force, forming a partially extended fiber structure; when the voltage is reduced, the stretching of the electrocoating jet is weakened, the fiber tends to break, and a short rod is formed. This periodic voltage regulation allows the short rod to be generated within a specified length range, and the size of the short rod can be further regulated by precisely controlling the period and amplitude of the voltage.
[0073] As another example, a gradual voltage reduction is performed to form particles.
[0074] The electric field uses a gradually decreasing voltage variation pattern to control the particle generation of the electrocoating liquid. As the voltage is gradually reduced from a relatively high initial value, the stretching force of the droplets gradually weakens, causing the electrocoating jet to transition from forming unstable fibers to a granular structure. At the beginning, the higher voltage ensures that the droplets can be formed and ejected, and as the voltage decreases, the droplets tend to shrink into more compact particles due to surface tension. By controlling the speed of voltage reduction and the final voltage value, the size and distribution of the particles can be precisely adjusted.
[0075] S130: Making the second fiber membrane into a blended yarn.
[0076] The second fiber membrane is made into lines, ropes, strips and other strips by extrusion, twisting, winding and the like, and then collected into rolls, piles or balls by convolution or stacking, and can also be further processed into yarns through conventional spinning processes.
[0077] The present invention uses an electrostatic coating method to attach a high molecular polymer to a natural fiber membrane in the form of an electrocoating liquid to form a second fiber membrane that mixes natural fibers and chemical fibers. The wettability of the high molecular polymer can enhance the functionality of the natural fiber, such as improving its toughness, wear resistance, antibacterial, antibacterial and anti-mite properties.
[0078] Preferably, the electrocoating solution is formed by mixing at least three substances, which include at least one solute or dispersant and at least one solvent or dispersant.
[0079] Solvent: Generally refers to a liquid that can dissolve solid, liquid or gaseous solutes. In the electrostatic coating process, the solvent helps to form a uniform solution or suspension to facilitate the application of thin films.
[0080] Solute: refers to a substance that can be completely or partially dissolved in a solvent to form a solution. In electrostatic coating, the solute is usually the material to be coated (such as a high molecular polymer).
[0081] Dispersant: A substance that contains the dispersed matter in the electrospinning state, helping the dispersed matter to be evenly distributed in the medium to avoid agglomeration or sedimentation. During the spinning or coating process, the dispersant can ensure the uniform dispersion of the dispersed matter.
[0082] Dispersoid: The dispersed substance in a dispersion system, which may be solid particles or liquid droplets, is distributed in the medium. In electrocoating fluids, the dispersoid is the material dispersed in the solvent or dispersant.
[0083] Examples of solvents and dispersants include methyl ether, isopropyl acetate, methyl formate, methylene chloride, ethyl ether, methyl propionate, isobutyl formate, butyl chloride, propyl ether, ethyl propionate, dichloroethane, isopentyl chloride, methanol, methyl carbonate, trichloroethane, carbon tetrachloride, ethanol, acetone, ethylene dichloride, carbon disulfide, propanol, 3-pentanone, dichloropropane, benzene, isopropyl alcohol, butanone, ethyl bromide, cyclohexane, ethyl acetate, 2-pentanone, dicarbonate, Methyl ester, butanol, 2-heptanone, sec-amyl acetate, 2-methoxyethyl acetate, isobutyl alcohol cyclohexanone, amyl propionate, furfural, sec-butanol, methyl cyclohexanone, isopropyl lactate, mesityl oxide, amyl alcohol, butyl acetate, diethyl carbonate, chlorobenzene, sec-amyl alcohol isobutyl acetate, ethylene glycol monoethyl ether, toluene, methyl amyl alcohol, sec-butyl acetate, ethylene glycol monomethyl ether, xylene, tetrahydrofurfuryl alcohol, methyl amyl acetate, ethylene glycol diethyl ether, 4- Heptanone, 5-methoxybutyl acetate, ethylene glycol monoisopropyl ether, 2-hexanone, amyl acetate, ethylene glycol monoacetate, benzyl alcohol, cyclohexanol, ethyl lactate, diethylene glycol monoethyl ether, 2-ethylhexanol diacetone, butyl butyrate, diethylene glycol monomethyl ether, furfuryl alcohol, diisobutyl (methyl) ketone, diethyl oxalate, diethylene glycol diethyl ether, diacetone alcohol, cyclohexyl acetate, ethyl benzoate, methoxydiglycol acetate, methyl hexanol, 2-acetic acid Ethyl butyl ester, ethylene glycol monobutyl ether, butoxydiglycol acetate, isophorone furfuryl acetate, ethylene glycol monobenzyl ether, ethylene glycol diacetate, dichloroethyl ether, ethyl acetoacetate, 2-butoxyethyl acetate, diethylene glycol diacetate, glacial acetic acid, N-methylpyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, hexafluoroisopropanol, dimethyl sulfoxide, acetic anhydride, turpentine, tetrahydrofuran, dioxane, water, etc.
[0084] In the case where the electrocoating liquid is formed by mixing at least three substances, the at least three substances are mixed and formed into the electrocoating liquid before being supplied.
[0085] The mixing method of the electro-coating liquid includes: the electro-coating liquid provided by at least two liquid containing boxes 144 is mixed during the liquid supply process; the electro-coating liquid provided by at least two liquid containing boxes 144 is instantly contacted and sprayed out when the liquid is discharged; the electro-coating liquid provided by at least two liquid containing boxes 144 forms a core-sheath structure in which the sheath liquid surrounds the core liquid when spraying.
[0086] Preferably, the electrocoating liquid can be a solution, or a sol, a suspension or an emulsion.
[0087] Sol (colloid): It is a relatively uniform mixture containing two different phases of matter: dispersed phase and continuous phase. The dispersed phase is composed of tiny particles or droplets, and the diameter of these particles is usually between 1 and 100 nanometers. In the colloid, the size of the dispersed particles is between the coarse dispersion system and the true solution, thus forming a highly dispersed multiphase inhomogeneous system. For example, nano-length carbon nanotubes are used as coating carriers, and povidone-iodine is coated to form a povidone-iodine sustained-release electrocoating solution, which is directly used for electrocoating after preparation.
[0088] Suspension: A suspension is a mixture in which insoluble solid particles are suspended in a liquid. These particles are usually larger than 100 nanometers in diameter. This makes suspensions often turbid and opaque.
[0089] Emulsion: An emulsion is a dispersed system consisting of two immiscible liquids, one of which is dispersed in the other in the form of small droplets. The dispersed phase is stabilized by stirring and emulsifiers.
[0090] For example, polymer emulsions can be used for electrostatic coating to form nanofibers. Such emulsions are usually composed of polymer particles (such as polyacrylates, polyurethanes, etc.) dispersed in water or organic solvents. Through the electrostatic coating process, these emulsions can be converted into nanofibers with uniform diameters, which are widely used in filtration, adsorption, biomedicine and other fields.
[0091] Water-in-oil emulsions (W / O emulsions) can be used for electrostatic coating, but their main application is not only to prepare hydrophobic fibers. By dispersing the water phase (containing water-soluble polymers or other functional components) in the oil phase, water-in-oil emulsions can form fibers with multilayer structures or core-shell structures during the electrostatic coating process. This structure can give natural fibers special properties, such as hydrophobicity, hydrophilicity, controlled release characteristics, etc. Therefore, water-in-oil emulsions can be used not only for waterproof materials or textiles, but also for drug delivery systems, smart response materials, etc.
[0092] Oil-in-water emulsions (O / W emulsions) can be used to make fibers with controlled release properties. In this emulsion, the oil phase (containing hydrophobic chemicals or drugs) is encapsulated by the water phase to form a microcapsule structure. Through the electrostatic coating process, these microcapsules can be embedded inside natural fibers to form fibers with controlled release functions. This type of fiber is not only suitable for drug delivery systems, but can also be used in the fields of aromatic fibers, slow-release pesticides, cosmetics, etc. In addition, oil-in-water emulsions can also be used to prepare fibers with a dual-continuous phase structure, further expanding its scope of application.
[0093] Preferably, the electrocoating liquids provided by at least two liquid storage boxes 144 are mixed during the liquid supply process. Different electrocoating liquids can add different functions. Therefore, when mixing two different electrocoating liquids does not affect the functionality, it is suitable to mix the two electrocoating liquids before spraying.
[0094] Preferably, the electrocoating liquids provided by at least two liquid storage boxes 144 are in contact and sprayed out immediately when the liquids are discharged. This method is suitable for electrocoating liquids that strictly require mixing to be completed in a very short time to minimize the influence of mutual reactions.
[0095] Preferably, the electrocoating liquid provided by at least two liquid storage boxes 144 forms a core-sheath structure in which the sheath liquid surrounds the core liquid when sprayed. This spraying method requires a special nozzle structure to cooperate. The nozzle 110 can adopt a large and small sleeve structure to optimize the pipeline layout, so that the nozzle 110 can generate nanoscale fibers with a unique wrapping structure. Specifically, the nozzle 110 is tightly connected to the pipelines of the two liquid storage boxes 144 through large and small sleeves, and one of the electrocoating liquids serves as the core liquid and flows in the internal pipeline. The other electrocoating liquid serves as the sheath liquid, surrounds the outside of the core liquid, and flows through the external pipeline. When the two electrocoating liquids meet inside the nozzle 110, they are not simply mixed, but form a fiber with a core-sheath structure through the natural wrapping mechanism of fluid dynamics. This structure allows the core liquid to be completely surrounded by the sheath liquid, thereby achieving effective protection of the core liquid and enhancing its function.
[0096] The electrostatic coating method has advantages that the electrostatic spinning method does not have:
[0097] First, the existing technology mainly focuses on the advantages of electrospinning in forming fine fibers that cannot be formed by conventional methods, but often ignores its advantages in preparing nanoscale short rods. This short rod structure is conducive to the riveting between chemical fibers and natural fibers during the electrocoating process, thereby enhancing the functionality of natural fibers.
[0098] In the implementation process of electrostatic coating, the characteristics of the bead string structure have obvious advantages. In the case of unstable voltage, the uneven polymer solution is caused by the uneven electrocoating jet, thereby forming a bead string structure. In the bead string structure, the short rods are difficult to solidify in the same time, so there is enough time to wrap the natural fiber and rivet it in the natural fiber. This riveting is not only conducive to the combination of functional nano-scale polymer materials and natural fibers, but also significantly reduces the possibility of separation from the natural fiber under the action of macroscopic external forces. Preferably, when the polymer material is controlled and dispersed on the surface of the first fiber membrane, functional reaction sites are formed. At this time, the second fiber membrane has formed a fiber membrane with reaction sites.
[0099] In addition, during the electrocoating process, when functional active substances are added to natural fibers, some polymers can form wettability fixation on natural fibers. This fixation can not only enhance the aggregation of natural fibers, but also embed more functional substances into natural fibers, thereby enhancing the antibacterial, antibacterial and / or anti-mite functions of natural fibers, that is, enhancing the stability of additives and natural fibers.
[0100] As mentioned above, the electrostatic coating method not only has advantages in forming fine fibers, but also has advantages that the electrospinning method does not have in preparing nanoscale short rods, enhancing the functionality of natural fibers, and improving the stability of electrocoating.
[0101] Preferably, the electrocoating solution is formulated to match the properties of the natural fiber.
[0102] The present invention appropriately adjusts the formula parameters of the electrocoating solution for electrocoating natural fibers according to the properties of the natural fibers themselves. The adjustment strategy will also vary for different natural fibers, but the essential purpose is to ensure that the natural fibers have certain functionality while adjusting the chemical fibers so that the properties of the natural fibers can be maintained as much as possible during use.
[0103] Properties of natural fibers: Polyurethane materials have good adhesion properties, but poor toughness, so they are easy to adhere to the surface of natural fibers, which allows polyurethane materials to be used as additives on natural materials that have high strength but are difficult to combine with chemical materials and fibers, such as bamboo fibers, hemp fibers, etc.; while polyacrylonitrile materials have strong toughness, but poor adhesion properties, which allows polyacrylonitrile materials to be added to fibers with relatively loose natural structures, so that when the natural fibers of the substrate 500 are subjected to large external forces and produce macroscopic deformation, the structural characteristics of the nanofibers are not destroyed. Polyacrylonitrile materials are, for example, loose cotton fibers, wool fibers, etc.
[0104] Physical properties of natural fibers: Finer natural fibers mean larger specific surface area, which is in great demand in the fields of filtration materials, catalyst carriers, tissue engineering scaffolds, etc., because a larger surface area can provide more reaction sites and enhance reaction activity, which is particularly effective for antibacterial and deodorizing materials with catalyst types such as nanosilver, copper oxide, zinc oxide, etc.; while thicker fibers mean higher loading capacity, which will produce better advantages for antibacterial and deodorizing materials that require sustained release effects, because thicker fibers can carry larger sustained-release particles and units, and can continuously release antibacterial and deodorizing materials for a longer period of time.
[0105] The present invention is of great significance in matching chemical fiber with natural fiber. If a polymer material with stronger fiber performance is used on fibers that are difficult to combine with other materials such as bamboo fiber and hemp fiber, the chemical fiber coated with electrostatic coating will not be tightly combined with the natural fiber, which will lead to the desorption of chemical fiber and natural fiber during subsequent processing or use, affecting the effect of the components in the chemical fiber. If a finer fiber layer is coated on a fiber with better toughness or a fiber that is easy to slide, the fine chemical fiber layer will break under external force, causing the chemical fiber layer to be more easily separated from the natural fiber layer, reducing the efficiency of fiber production. If a coarse fiber film is coated on a fiber with better rigidity, not only will the color unevenness caused by different fiber types increase, but also the functional effects such as antibacterial and deodorization will decrease due to the reduction in specific surface area. Therefore, the proper matching of chemical fiber and natural fiber can achieve better results.
[0106] This embodiment uses a matching table of natural fibers and chemical fibers to show the effect of matching natural fibers and chemical fibers.
[0107] Matching table of natural fibers and chemical fibers:
[0108]
[0109] This example shows the difference in the effects achieved by the electrospinning method and the electrospinning method through a comparison table between electrospinning and electrospinning.
[0110] Comparison table of electrospinning and electrostatic coating:
[0111]
[0112] Example 2
[0113] This embodiment relates to a system for preparing functional blended yarns, such as Figure 1 to Figure 3 and Figure 7 As shown, the system includes an electrostatic coating device 100. The electrostatic coating device 100 can coat the nanoscale material to the substrate 500 as the first fiber membrane by electrostatic coating. The nanoscale material is a polymer containing additives, and the substrate 500 is a natural fiber material such as cotton, linen, and wool. The electrostatic coating device 100 can disperse and attach the nanoscale material to the first fiber membrane during the electrostatic coating process, so that the second fiber membrane made of natural fibers such as cotton, linen, and wool that do not have antibacterial, antibacterial and / or anti-mite functions has excellent antibacterial, antibacterial and / or anti-mite properties.
[0114] The polymer is a soluble polymer suitable for electrocoating, such as PU (polyurethane), TPU (modified polyurethane), PS resin, PPE resin, polyolefin, polyhalogenated olefin, polysiloxane, polyether, polyamide, polyester, polycarbonate, epoxy resin, polyacrylonitrile, polyacrylic polymer, polyphenylene ether, polyanhydride, poly-α-amino acid, polyphenylene sulfide, polyether sulfone, or a blend of two or more thereof, or one or more of the bioabsorbable synthetic polymer polylactic acid, chitin, chitosan, silk protein, poly-(D,L)-lactic acid, polyglycolic acid, polycaprolactone, polybutyrolactone, polyvalerolactone, polyester dioxane, polyanhydride, poly-α-amino acid, or a copolymer of at least two of the following monomers: L-lactic acid, (D,L)-lactic acid, glycolic acid, 3-hydroxybutyric acid, 3-hydroxyvaleric acid, caprolactone, butyrolactone, valerolactone, amino acid, or a blend of two or more thereof.
[0115] The additives are substances that have antibacterial, antibacterial and / or anti-mite effects, such as one or more of metal-organic frameworks, titanium dioxide, magnesium oxide, silver ion compounds, quaternary ammonium salt compounds, plant-based essential oils, povidone iodine, halamine compounds, medical antibiotics, amino acid antibacterial, antibacterial, anti-mite agents, and bacteriocins.
[0116] Preferably, during the electrostatic coating process, the electric field force acts on the charged nanoscale material, causing it to be ejected into an electrocoating jet and deposited on the substrate 500 to form a fiber film. The type and proportion of polymers and additives will affect the viscosity, surface tension and conductivity of the solution, thereby affecting the morphology of the fiber and the structure of the film. The potential difference is one of the key parameters in electrostatic coating, which affects the distribution of charge and the stability of the solution spraying. Different polymer and additive combinations may require different potential differences to optimize the formation and deposition of the fiber to achieve the desired fiber diameter and structural density. The spacing between the nozzle 110 and the substrate 500 will affect the flight distance and deposition pattern of the fiber. Adjustment of the spacing can change the arrangement and coverage density of the fibers on the substrate 500, thereby affecting the physical and mechanical properties of the final fiber film. Based on this, the electrostatic coating device 100 of the present invention can adjust the spacing and / or potential difference required for coating according to the type and / or proportion of the polymer and additives mixed in the nanoscale material, and increase the structural density of the nanoscale material deposited on the surface of the first fiber membrane, thereby providing more reaction sites on the surface of the first fiber membrane, thereby improving the antibacterial, antibacterial, anti-mite and other properties of the second fiber membrane.
[0117] By electrocoating nanoscale materials on the surface of natural fiber materials, the size, shape, dosage of additives, mass ratio to natural fibers, degree of wetting of natural fibers and other properties of the nanomaterials can be adjusted, so that the yarn or cloth made of natural fibers has good antibacterial, antibacterial and / or anti-mite properties while being evenly dyed, resistant to rubbing and washing.
[0118] Preferably, if Figure 1 As shown, the operating parameters of the electrostatic coating device 100 during the preparation of nanofibers are determined by the processing component 150. The processing component 150 can be a dedicated integrated chip or processor with a coding program of the adjustment method, which is integrated or installed in the electrostatic coating device 100.
[0119] The processing component 150 also stores in advance the parameter combination of coating spacing and potential difference required for electrostatic coating. When the type of polymer, the type of additive and the concentration relationship between the two are determined, the processing component 150 optimizes the electrostatic coating process by calling these parameter combinations to obtain a nanoscale fiber membrane with ideal antibacterial, antibacterial and / or anti-mite properties. Specifically, such a parameter combination can be obtained by the following experimental means:
[0120] 1. In the experimental design, the type of polymer, the type of additive, the concentration ratio of the two, the potential difference and the coating spacing are identified as the key factors affecting the fiber properties, among which the type of polymer is represented as P, the type of additive is represented as A, the concentration ratio is represented as C (expressed in weight percentage), the potential difference is represented as V (expressed in kilovolts), and the coating spacing is represented as D (expressed in centimeters).
[0121] 2. Design an experimental matrix to systematically vary these experimental variables. You can use full factorial experimental design or orthogonal experimental design methods to effectively cover a wide range of parameter spaces. Full factorial experimental design is able to test all possible combinations of all variables, while orthogonal experimental design reduces the number of experiments by selecting specific combinations while still being able to obtain sufficient valid data. In this way, the comprehensiveness and representativeness of the experimental results can be ensured, making subsequent data analysis more reliable.
[0122] 3. To prepare nanoscale materials, a series of polymer solutions with different compositions and concentrations need to be prepared according to the requirements of the experimental design. First, select a suitable solvent to ensure that the polymer is completely dissolved. Then, accurately weigh and mix the polymer and additives according to the proportions specified in the experimental design. In particular, when using additives, the amount of additives needs to be determined according to their properties in order to optimize the spinning performance of the solution.
[0123] 4. Adjust the potential difference and coating distance according to the values specified in the experimental design and perform electrostatic coating.
[0124] 5. After the electrostatic coating is completed, the collected fiber membrane is processed and its morphology and diameter are observed using a scanning electron microscope (SEM). In addition, the physical properties of the fiber membrane, such as mechanical properties, porosity and surface roughness, are tested, and these parameters can be used to evaluate the performance of the fiber. Taking the antibacterial, antibacterial and / or anti-mite performance test as an example, the plate method or agar diffusion method can be used to evaluate the antibacterial activity of the fiber membrane under different parameter combinations. In this process, a certain amount of bacterial culture medium can be prepared, and the fiber membrane can be placed on it to observe its inhibitory effect on the growth of surrounding microorganisms. Exemplarily, the relationship correspondence table gives the correspondence between the type of polymer, the type of additive, the concentration ratio of the two, the potential difference and the coating spacing.
[0125] Relationship table:
[0126]
[0127] Preferably, the processing component 150 can store the relationship correspondence table. When the type of polymer, the type of additive, and the concentration ratio of the two have been determined, the processing component 150 can quickly search the corresponding potential difference and coating spacing in the table of the relationship correspondence table, thereby realizing the parameter setting of the electrostatic coating device 100.
[0128] Preferably, the electrostatic coating device 100 can check the quality of the second fiber membrane that has been electrostatically coated, and optimize and adjust the preset potential difference and / or spacing based on the check result.
[0129] Preferably, the nozzle 110 is selected based on the properties of the polymer and the additive, and different types of nanoscale fibers can be formed using different nozzles 110. The purpose of selecting different types of nozzles 110 is to form different types of fibers, such as mixed fibers, wrapped fibers, etc., because different types of solutions may not dissolve in each other or react with each other. The liquid supply component 140 can be configured with multiple liquid boxes 144 to accommodate different combinations of polymers and additives. Figures 4 to 6 , the liquid supply assembly 140 is equipped with two liquid storage boxes 144 to form three different forms of nozzles 110 as an example for explanation.
[0130] Preferably, Figure 4The first form of the nozzle 110 is shown, which not only realizes the instant mixing of the polymer solution and the additive before being delivered to the nozzle 110 through the first liquid delivery pipeline 141, but also ensures that the two key components are fully and evenly mixed in the pipeline by selectively using a static mixer or a dynamic agitator to form the nanoscale fibers used later. The static mixer relies on its unique internal flow channel structure to achieve mixing by changing the flow direction of the fluid, dividing and reorganizing the fluid layer; while the dynamic agitator uses a mechanical stirring element to directly act on the fluid, for example, a fan blade structure with a stirring function can be used to accelerate the mixing process. Both can effectively reduce the mixing time and improve the mixing efficiency. In order to further optimize the mixing effect and prevent the nanoscale fibers from phase separation during the ejection process, the first form of the nozzle 110 is designed with special consideration of the flow path length of the mixed electrocoating liquid in the first liquid delivery pipeline 141. By increasing the necessary pipeline length, a longer interaction time is provided for the molecules or particles in the electrocoating liquid, thereby promoting more thorough mixing and ensuring that the nanoscale fibers have reached a highly uniform state when they reach the nozzle 110.
[0131] Preferably, Figure 5 The second form of the nozzle 110 is shown, and the pipeline design between the nozzle and the two liquid boxes 144 of the liquid supply assembly 140 realizes the process of two electrocoating liquids (usually polymers and additives) being efficiently sprayed after almost instantaneous contact. This design is designed for systems that strictly require mixing to be completed in a very short time to minimize the impact of mutual reactions. In such applications, shortening the mixing time is a key factor in ensuring the quality and characteristics of the final product. To achieve the above goals, in the second form of the nozzle 110 design, as shown in FIG. Figure 5 As shown, a second liquid infusion pipe 142 with a bent structure is embedded in the connecting pipe between at least one liquid storage box 144 and the nozzle 110. This technical feature accurately controls the flow direction of the electrocoating liquid in the liquid storage box 144, and significantly reduces the mixing intensity between the additive and the polymer by optimizing the mixing method, thereby effectively avoiding unnecessary chemical reactions and ensuring the ideal properties of the final product such as nanoscale fibers. Specifically, the bent second liquid infusion pipe 142 causes the electrocoating liquids in the two liquid storage boxes 144 to meet in tangential flow directions before mixing. Compared with the relative flow mixing method in the first form of the nozzle 110, the tangential mixing significantly reduces the force during the mixing process and reduces the direct collision and turbulence between the electrocoating liquids. This gentle mixing mechanism effectively avoids liquid splashing, foam generation, and possible chemical reactions, ensuring the stability and controllability of the mixing process.
[0132] In addition, through careful optimization of the pipeline layout, the mixing point is precisely set at a position close to the outlet of the nozzle 110. This layout greatly shortens the flow path of the liquid from the liquid storage box 144 to the mixing point and then to the nozzle 110, significantly reducing the time required for mixing. In systems that require rapid response control, this design has obvious advantages because it can effectively prevent the problem of changes in liquid properties or reduced reaction efficiency due to excessive mixing time. At the same time, the mixing point close to the nozzle 110 also ensures that the mixed liquid can be sprayed out quickly and evenly, further improving the mixing effect and the immediacy of the reaction.
[0133] Preferably, Figure 6 The third form of the nozzle 110 is shown, which uses a third liquid delivery pipeline 143 of large and small sleeves to optimize the pipeline layout. This design enables the nozzle 110 to generate nanoscale fibers with a unique wrapping structure. Specifically, the nozzle 110 is tightly connected to the pipelines of the two liquid storage boxes 144 through large and small sleeves. One of the electrocoating liquids serves as the core liquid and flows in the internal pipeline; while the other electrocoating liquid serves as the sheath liquid, surrounding the outside of the core liquid and flowing through the external pipeline. When the two electrocoating liquids meet inside the nozzle 110, they are not simply mixed, but through the natural wrapping mechanism of fluid dynamics, a fiber with a core-sheath structure is formed. This structure allows the core liquid to be completely surrounded by the sheath liquid, thereby achieving effective protection of the core liquid and enhancing its function.
[0134] The nozzle 110 design under this form, its mixing mode completely depends on the natural flow and interaction of the fluid in the pipeline, without the need for additional mixing devices or mechanical forces. Therefore, the mixing time is mainly determined by the flow velocity of the electrocoating liquid inside the nozzle 110 and the design parameters of the nozzle 110 (such as pipeline diameter, length, curvature, etc.). By accurately controlling these parameters, it is possible to achieve fine regulation of the mixing process, thereby producing nanoscale fibers with specific riveting structures and properties. Preferably, in the material preparation stage, the polymer and additives can be mixed in a dedicated static mixer, and the static mixer is equipped with a high-speed stirring paddle and a temperature control system to ensure that the materials are mixed evenly and prevent material degradation. The temperature control system allows the electrocoating liquid to enter the liquid supply assembly 140 after being heated or cooled. The stirring speed and temperature of the static mixer are accurately adjusted according to the characteristics of the polymer and the additive. The liquid supply assembly 140 is responsible for delivering the uniformly mixed electrocoating liquid to the nozzle 110. The nozzle 110 includes a precision pump and a flow meter to adjust the electrocoating liquid supply rate. A micro-agitator is provided at the connection of the spray head 110 to prevent the electrocoating liquid from settling or stratifying. The spray head 110 is designed to be replaceable to adapt to different coating modes and electrocoating liquid characteristics, ensuring seamless connection with the liquid supply component 140.
[0135] Preferably, if Figure 1 to Figure 3As shown, the electric field control component 130 of the electrostatic coating device 100 is composed of a plurality of electrodes, which can form a uniform electrostatic field, guide the electrocoating liquid to form fibers and accurately deposit on the substrate 500. The intensity and shape of the electric field are precisely controlled by the voltage regulator and current feedback system of the high-voltage power supply to meet different electrocoating requirements.
[0136] Preferably, during the electrostatic coating process, the distance between the nozzle 110 and the receiving end 120 for guiding and transmitting the first fiber membrane is adjusted in micrometers by a displacement control unit driven by a stepper motor to ensure the uniformity and density of fiber deposition. The position and shape of the electric field control component 130 can also be adjusted to adapt to different electrocoating widths and fiber orientations. After the electrostatic coating is completed, the quality inspection of the second fiber membrane is performed by a series of high-precision detection instruments. High-precision detection instruments include optical microscopes, surface profilers, and antibacterial performance testing devices. The data provided by these detection instruments are fed back to the control system in real time, triggering an automatic adjustment mechanism to optimize parameters such as potential difference, nozzle 110 position, and liquid supply rate.
[0137] Preferably, the detection instrument automatically selects the most suitable combination of nozzles 110 for coating operations by real-time analysis of the rheological properties, conductivity and required fiber properties of the electrocoating liquid. This algorithm can accurately control the activation order and duration of each group of nozzles 110 according to a preset program to meet the needs of different material properties and electrocoating effects. For example, for fiber membranes that require multiple layers of superposition, the processing component 150 and the control system will enable different groups of nozzles 110 in turn to achieve simultaneous deposition and layer-by-layer construction of multiple layers of fibers. In addition, the processing component 150 in the electrostatic coating device 100 can also dynamically adjust the working state of the nozzle 110 through the control system based on the real-time feedback data from the detection instrument to compensate for any deviations that may occur during the process.
[0138] Preferably, the electrostatic coating device 100 is also equipped with a detection component 160 for verifying the quality of the finished product of the second fiber membrane after electrostatic coating. The detection component 160 adopts a modular and highly automated integrated solution, which is equipped with a high-precision detection tool specifically for fiber membrane quality monitoring and has a special detection capability for the surface uniformity of the second fiber membrane. This function is achieved through an integrated high-resolution imaging system or laser scanning technology, which can meticulously check the surface of the second fiber membrane to ensure that there are no obvious unevenness, fiber aggregation or other surface defects.
[0139] During the testing process, the testing component 160 not only continuously monitors the uniformity of the fiber membrane thickness using a thickness gauge to ensure that it is within the predetermined specification range, but also uses a surface roughness measuring instrument to deeply evaluate the microscopic morphology of the fiber surface. In addition, the introduction of the antibacterial performance testing device simulates the actual application scenario and conducts a comprehensive and accurate evaluation of the antibacterial, antibacterial and / or anti-mite performance of the second fiber membrane, further ensuring the functionality and safety of the product.
[0140] It is particularly worth mentioning that the detection component 160 can respond quickly when it identifies that there is a deviation in the surface uniformity of the second fiber membrane. The real-time data transmitted from the high-speed data bus is precisely processed through the analysis results and compared with the preset high-quality standards. Once any non-uniformity problem that may affect the product quality is detected, the detection component 160 has an adjustment mechanism that automatically provides feedback to the processing component 150. This mechanism includes but is not limited to dynamically adjusting the potential difference and the spray spacing to optimize the charge distribution to ensure that the fiber membrane obtains uniform charge coverage during electrostatic coating or other production processes; at the same time, it can also involve fine-tuning the position of the nozzle 110 and precise control of the liquid supply rate, thereby comprehensively improving the molding quality and surface uniformity of the fiber membrane from multiple dimensions.
[0141] Preferably, the slide rail element of the electric field control component 130 adopts precision manufacturing technology and has extremely high positioning accuracy and load-bearing capacity, ensuring that the nozzle 110 or the receiving end 120 can achieve millimeter-level precise movement in three-dimensional space. The design of the transmitting electrode 131 and the receiving electrode 132 adopts a modular structure, which can be quickly disassembled and replaced to adapt to the requirements of electric fields of different shapes and intensities. The electrode material is made of an alloy with high conductivity and corrosion resistance to ensure the stability and long-term durability of the electric field. In addition, the electric field control component 130 is also equipped with a fine-tuning mechanism that allows the operator to make micron-level adjustments according to actual conditions to optimize the deposition pattern and orientation of the fiber.
[0142] Preferably, if Figure 7 As shown, the electrostatic coating device 100 further includes a transmission device 200 , a processing device 300 and a collecting device 400 .
[0143] The design of the transmission device 200 adopts a high-efficiency and high-stability servo motor as the driving system. Through precise electronic control, the second fiber membrane is steplessly regulated and precisely positioned, ensuring the stability and uniformity of the second fiber membrane during transportation. The processing device 300 integrates precise cutting and forming tools, which can be adjusted according to the width and thickness of the fiber membrane to achieve high-precision cutting and forming. The design of the collection device 400 adopts flexible materials and structures, which can protect the fiber membrane from damage while convoluting or stacking the finished product, ensuring the integrity and stability of the product. In addition, the processing device 300 can squeeze, twist, wind, etc. the second fiber membrane into strips such as lines, ropes, and strips, and transport the processed strips to the collection device 400 and collect them in a convoluted or stacked manner, and collect the lines and ropes into rolls, piles or balls, etc.
[0144] Preferably, the ultraviolet lamp, temperature control device and pressing assembly in the processing device 300 constitute an intelligent post-processing system, which can be automatically adjusted according to the characteristics and post-processing requirements of the second fiber membrane. The intensity and irradiation time of the ultraviolet lamp can be adjusted according to the type and concentration of the photosensitizer in the second fiber membrane to achieve the best antibacterial, antibacterial and / or anti-mite effect and curing effect. The temperature control device adopts precise temperature control technology, which can simulate different ambient temperatures to meet the heat treatment requirements of different materials. The pressing assembly can adjust the pressure and pressing time according to the thickness and hardness of the fiber membrane to ensure that the second fiber membrane achieves the required physical properties after pressing. The entire post-processing system realizes intelligent adjustment and optimization through communication with the processing assembly 150, further improving the quality and performance of the product. The pressing assembly processes the second fiber membrane through one or more of normal temperature pressing, cooling pressing, hot pressing, ultrasonic pressing, gluing, and compounding, and then enters the collection device 400. The processing device 300 should also integrate safety mechanisms such as emergency stop buttons, overload protection and leak detection to ensure safe operation. In addition, the environmental control system at the site where the electrostatic coating device 100 is located should maintain stable humidity and temperature to prevent electrostatic interference and changes in material properties.
[0145] Additives are added to the electrocoating solution to play a functional role, such as adding antibacterial solution, such as electrocoating solution containing silver or silver ions, polyethyleneimine antibacterial functionalized electrocoating solution. Adding antibacterial solution can play an antibacterial role.
[0146] Preferably, the novel composite antibacterial and mite-removing agent of chitosan can play a role in removing mites.
[0147] Preferably, adding chloramine polymer and one or more solutions of wormwood extract, Houttuynia cordata extract, Phellodendron chinense extract, Indigo naturalis extract and Tonka cordata extract, silver-containing compounds and zirconium phosphate compounds, and polyurethane polymers can achieve a deodorizing effect.
[0148] Preferably, adding a mildew-killing agent, such as calcium phosphate and 2-pyridinethiol-1-zinc oxide, can have an anti-mildew effect.
[0149] Preferably, adding metal fibers, softeners and antistatic agents in combination with polyurethane, polyacrylonitrile / phenyl acrylate copolymer, nano-ceramic absorbent and nano-conductive polymer can play an anti-radiation effect, etc.
[0150] Preferably, adding a polymer permanent antistatic agent can achieve an antistatic effect.
[0151] Preferably, a film-forming aid is added to impart underwater superoleophobicity to the electrostatically coated surface, and oily stains on the electrostatically coated surface can be quickly removed by washing with water, and the film itself has excellent optical transparency, biocompatibility and excellent wearing comfort.
[0152] Generally, one additive can play multiple roles. Specifically, the following are several experiments to study the antibacterial, antibacterial and / or anti-mite effects of the antibacterial material obtained by using the system for preparing microbial control functional nanofibers of the present invention:
[0153] Experiment 1:
[0154] Dissolve 1 to 3 parts of silver nitrate solution and 7 to 11 parts of polyacrylonitrile in 100 parts of N, N-dimethylformamide, stir at room temperature for 16 hours, and mix well to obtain an antibacterial solution.
[0155] An antibacterial solution is used to electrostatically coat the substrate 500, and the electrostatic coating process parameters are: the electrostatic coating applied voltage is 5 to 35 KV, the receiving distance is 10 to 30 cm, the spinning temperature is 18 to 22°C, the ambient relative humidity is 30 to 40%, the drum speed is 20 to 300 rpm, and the fiber membrane carrier is cotton yarn to obtain antibacterial cotton yarn.
[0156] The agar plate diffusion method was used to test the antibacterial effects of cotton yarn with antibacterial materials (Group A) and without antibacterial materials (Group B) on Pseudomonas aeruginosa and Staphylococcus aureus. Weigh 3.6NB nutrient powder, add 200ml deionized water, heat to dissolve, adjust the pH value to 7.2-7.4, sterilize at 115℃ for 30min, and incubate in a 37℃ incubator overnight to obtain the test strains. Discs (1cm in diameter) of different fiber samples were placed on the solidified agar gel of different culture dishes and incubated at 37℃ for 48h.
[0157] Table 1 Antibacterial ability test of antibacterial materials against Pseudomonas aeruginosa
[0158]
[0159] Table 2 Antibacterial ability test of antibacterial materials against Staphylococcus aureus
[0160]
[0161] The results showed that after adding antibacterial material fibers, the test cotton yarn produced significant antibacterial rings against Pseudomonas aeruginosa and Staphylococcus aureus, and the widths of the antibacterial bands reached 6mm and 7mm respectively, with good antibacterial effects. Cotton yarn without adding antibacterial materials did not produce antibacterial rings.
[0162] The inhibition zone refers to a narrow band of inhibition of bacterial growth formed when the antibiotic diffuses from the paper or agar strip containing it into the agar plate in a test such as the disc diffusion method or the agar strip diffusion method. The width of this band can also reflect the effectiveness of the antibiotic, but it is usually narrower than the inhibition ring and the shape may not always be a perfect circle. For example, in the case where the average value of the inhibition ring diameter is 22mm, the radius of the inhibition ring is 5+6mm. Then the width of the inhibition zone is 6mm.
[0163] Take a 20g sample from the large sample of antibacterial fabric and use AATCC1993WOB non-phosphate standard detergent with a concentration of 0.2%. Add 6L of 40±3℃ hot water, 20g of sample and 180g of fabric to be washed, and 12g of detergent to the washing machine, and start washing for 25min. Drain the water and wash with 6L of tap water for 2min. Take out the fabric and centrifuge for dehydration for 1nmin. Wash with 6L of tap water for 2min again, take out the fabric and centrifuge for dehydration for 1nmin. Repeat this procedure until the specified number of washes. In order to prevent residual detergent from interfering with the antibacterial performance test, the sample is thoroughly cleaned at the end of the last procedure, and then dried to obtain sample A′, repeat the above process twice to obtain sample A″, repeat the above process 4 times to obtain sample A″′, and the antibacterial ability of samples A′, A″, and A″′ against two strains is tested, and the results are as follows.
[0164] Table 3 Antibacterial ability test of antibacterial materials against Pseudomonas aeruginosa
[0165] Test points 1 2 3 A′ group inhibition ring (mm) 21 21 21 A″ group antibacterial ring (mm) 20 21 21 A″′ group antibacterial ring (mm) 20 20 19
[0166] Table 4 Antibacterial ability test of antibacterial materials against Staphylococcus aureus
[0167] Test points 1 2 3 A′ group inhibition ring (mm) 25 24 24 A″ group antibacterial ring (mm) 24 24 24 A″′ group antibacterial ring (mm) 23 24 23
[0168] The results showed that after the antibacterial material fiber was washed according to the national standard requirements, the tested cotton yarn still had significant antibacterial rings against Pseudomonas aeruginosa and Staphylococcus aureus, proving that washing has little effect on the antibacterial properties of natural fibers treated with electrostatic coating, and the fibers can still maintain good antibacterial properties after washing.
[0169] A secondary dyeing experiment was carried out, and the antibacterial fiber membrane obtained in the experiment was dyed evenly, and there was no obvious color block deposition after washing.
[0170] Experiment 2:
[0171] 1 to 3 parts of graphene-loaded silver nanoparticles, 0.2 to 2 parts of quaternary ammonium salt antibacterial components and 9 to 15 parts of polyurethane are dissolved in 100 parts of N, N-dimethylformamide, stirred at room temperature for 8 hours, and mixed evenly to obtain an antibacterial liquid.
[0172] An antibacterial solution is used to electrostatically coat the substrate 500, and the electrostatic coating process parameters are: the electrostatic coating applied voltage is 5-40KV, the receiving distance is 5-35cm, the spinning temperature is 20-25℃, the environmental relative humidity is 30-40%, the drum speed is 20-200rpm, and the fiber membrane carrier is long-staple cotton yarn to obtain antibacterial cotton yarn.
[0173] The agar plate diffusion method was used to test the antibacterial effects of cotton yarn with added antibacterial materials (Group A) and without added antibacterial materials (Group B) on Staphylococcus aureus and Escherichia coli, and the antibacterial ring diameter was tested. The results are as follows.
[0174] Table 1 Antibacterial ability test of antibacterial materials against Staphylococcus aureus
[0175]
[0176] Table 2 Antibacterial ability test of antibacterial materials against Escherichia coli
[0177]
[0178] It can be seen from the data that the silver-containing nanofiber membrane prepared by electrostatic coating has obvious antibacterial effect on Staphylococcus aureus and Escherichia coli.
[0179] Take a 20g sample from the large sample of antibacterial fabric and use AATCC1993WOB non-phosphate standard detergent with a concentration of 0.2%. Add 6L of 40±3℃ hot water, 20g of sample and 180g of fabric to be washed, and 12g of detergent to the washing machine, and start washing for 25min. Drain the water and wash with 6L of tap water for 2min. Take out the fabric and centrifuge for dehydration for 1min. Wash with 6L of tap water for 2min again, take out the fabric and centrifuge for dehydration for 1min. Repeat this procedure until the specified number of washes. In order to prevent residual detergent from interfering with the antibacterial performance test, the sample is thoroughly cleaned at the end of the last procedure, and then dried to obtain sample A′, repeat the above process twice to obtain sample A″, repeat the above process 4 times to obtain sample A″′, and test the antibacterial ability of samples A′, A″, and A″′ against two strains. The results are as follows.
[0180] Table 3 Antibacterial ability test of antibacterial materials against Staphylococcus aureus
[0181] Test points 1 2 3 A′ group inhibition ring (mm) 18 18 17 A″ group antibacterial ring (mm) 18 17 18 A″′ group antibacterial ring (mm) 18 17 17
[0182] Table 4 Antibacterial ability test of antibacterial materials against Escherichia coli
[0183] Test points 1 2 3 A′ group inhibition ring (mm) 18 18 19 A″ group antibacterial ring (mm) 18 19 18 A″′ group antibacterial ring (mm) 18 18 18
[0184] The results showed that after the antibacterial material fiber was washed according to the national standard, the tested cotton yarn still had significant antibacterial rings against Staphylococcus aureus and Escherichia coli, proving that washing has little effect on the antibacterial properties of natural fibers treated with electrostatic coating, and the fibers can still maintain good antibacterial properties after washing.
[0185] Experiment 3:
[0186] Dissolve 0.2-3 parts of povidone iodine and 5-15 parts of polyurethane in a mixed electrocoating liquid of 80-100 parts of N,N-dimethylformamide and 10-30 parts of hexafluoroisopropanol, stir at room temperature for 12-14 hours, and mix evenly to obtain an antibacterial liquid.
[0187] An antibacterial solution is used to electrostatically coat the substrate 500, and the electrostatic coating process parameters are: the electrostatic coating applied voltage is 5-50KV, the receiving distance is 5-45cm, the spinning temperature is 10-15°C, the environmental relative humidity is 30-45%, the drum speed is 20-250rpm, and the fiber membrane carrier is cotton yarn to obtain antibacterial cotton yarn.
[0188] The agar plate diffusion method was used to test the antibacterial effects of cotton yarn with antibacterial materials (Group A) and without antibacterial materials (Group B) on Pseudomonas aeruginosa and Escherichia coli and the diameter of the antibacterial ring. Weigh 3.6NB nutrient powder, add 200ml deionized water, heat to dissolve, adjust the pH value to 7.2-7.4, sterilize at 115℃ for 30min, and incubate in a 37℃ incubator overnight to obtain the test strains. Discs (1cm) of different fiber samples were placed on the solidified agar gel of different culture dishes and incubated at 37℃ for 48h.
[0189] Table 1 Antibacterial ability test of antibacterial materials against Pseudomonas aeruginosa
[0190]
[0191] Table 2 Antibacterial ability test of antibacterial materials against Escherichia coli
[0192]
[0193] The results showed that after adding antibacterial material fibers, the test cotton yarn produced significant antibacterial rings against Pseudomonas aeruginosa and Escherichia coli, and the widths of the antibacterial bands reached 4mm and 5mm respectively, with good antibacterial effects. Cotton yarn without added antibacterial materials did not produce antibacterial rings. At the same time, the experiment found that this antibacterial fiber also has a mite removal effect.
[0194] Experiment 4:
[0195] Dissolve nano-titanium dioxide and chitosan in glacial acetic acid, stir at room temperature, mix evenly to obtain an antibacterial liquid, and spray it on the substrate 500 to obtain an antibacterial material A;
[0196] Electrostatic coating is performed on the antibacterial material A, and the electrostatic coating process parameters are: the electrostatic coating applied voltage is 5-20KV, the receiving distance is 10-15cm, the spinning temperature is 23-27°C, the relative humidity of the environment is 25-35%, and the coating carrier of the electro-coating liquid is polyurethane. After electrostatic coating, the antibacterial material B is obtained.
[0197] The performance of the two antibacterial materials was tested at 10 points. The antibacterial materials (2 cm 2 ×2cm 2 ), take 100 μl of mutans streptococcus solution on the antibacterial material, evenly spread it, and place it in a carbon dioxide incubator for 48 hours. Scan the diluted coated plate and calculate the antibacterial property, that is, the number of microbial killing logs = 1g (blank control group colony technology / experimental colony count). The results of the antibacterial performance of mutans streptococci are as follows:
[0198]
[0199] It can be seen from the data that the fiber membrane formed by electrostatic coating has no significant effect on the antibacterial function.
[0200] Cut the antibacterial material (2cm) under constant temperature (25℃) 2 ×2cm 2 ), placed in a sterile container, blow carbon dioxide to the antibacterial material to simulate air filtration. Take 100μl of Streptococcus mutans solution on the antibacterial material, spread it evenly, and place it in a carbon dioxide incubator for 48 hours. Scan the diluted coated plate and calculate the antibacterial property, that is, the number of microbial killing = 1g (blank control group colony technology / experimental colony count). The results of the antibacterial performance of Streptococcus mutans are as follows:
[0201]
[0202] It can be seen from the data that the fiber membrane formed by electrostatic coating can protect the antibacterial function of the material.
[0203] After the two fiber membranes were placed in the culture dish for 5 days, they were washed with sterilized water and the antibacterial properties were tested again. The experimental results showed that the fiber membrane in group B still had good antibacterial properties.
[0204] Experiment 5:
[0205] Antibacterial fibers were prepared using inorganic particles as antibacterial agents. Silane coupling agents were used to prevent inorganic particles from sticking together. Nano-scale inorganic particles were added to the electrocoating solution, and ultrasonic dispersion was used to evenly disperse the particles. The electrocoating solution was spun. Group A was spun directly from the above solution, and Group B was further stirred by adding a stirring device using this method.
[0206] In this experiment, titanium dioxide is selected as the antibacterial agent, polylactic acid solution is selected as the electrocoating liquid, titanium dioxide is colored with a colorant, and the spinning effect is observed. Antibacterial performance test: Staphylococcus aureus is used as the test strain. The experimental results are as follows:
[0207]
[0208] The experiment shows that adding antibacterial inorganic particles to the polymer can make the fiber antibacterial, and the distribution uniformity of the antibacterial particles in group B is more uniform than that in group A.
[0209] Experiment 6
[0210] In the experiment group A, the antibacterial polymer was directly electrostatically coated, and in the experiment group B, the electrostatic coating was performed by coaxial electrospinning. Nanocuprous oxide powder was dispersed in deionized water, ultrasonicated for 2 hours, and silk protein solution was added. The polymer was polyethylene oxide solution. The spinning voltage was 10-12KV; the receiving distance was 12-17cm.
[0211] The antibacterial performance of the two antibacterial fibers A\B was tested at 5 points. After the two antibacterial fibers were subjected to a sterile air filtration simulation test, the antibacterial performance of the antibacterial fibers A'\B' was tested at 5 points. The results are as follows:
[0212]
[0213] It can be seen from the experiment that the coaxial electrospinning method can ensure the antibacterial function and have good stability.
[0214] Experiment 7:
[0215] After the electrostatic coating device 100 generates the polyvinylidene fluoride fiber membrane and performs plasma treatment, it slowly enters the processing section, where a 4-vinylpyridine isopropanol solution containing device or spraying device is set to fully immerse the polyvinylidene fluoride fiber membrane in the isopropanol solution. Then, an ultraviolet lamp is used in the processing section to irradiate the fiber membrane, and the temperature control device is adjusted to 70° to accelerate the quaternization reaction of the active ingredient. The results are as follows:
[0216]
[0217] It can be seen from the experiment that the use of ultraviolet light can enhance the antibacterial function.
[0218] Experiment 8:
[0219] 1 to 3 parts of graphene-loaded silver nanoparticles, 0.2 to 2 parts of quaternary ammonium salt antibacterial components and 9 to 15 parts of polyurethane are dissolved in 100 parts of N, N-dimethylformamide, stirred at room temperature for 8 hours, and mixed evenly to obtain an antibacterial liquid.
[0220] An antibacterial solution is used to electrostatically coat the substrate 500, and the electrostatic coating process parameters are: the electrostatic coating applied voltage is 5-40KV, the receiving distance is 5-35cm, the spinning temperature is 20-25℃, the environmental relative humidity is 30-40%, the drum speed is 20-200rpm, and the fiber membrane carrier is long-staple cotton yarn to obtain antibacterial cotton yarn.
[0221] The agar plate diffusion method was used to test the antibacterial effects of cotton yarn with added antibacterial materials (Group A) and without added antibacterial materials (Group B) on Staphylococcus aureus and Escherichia coli, and the antibacterial ring diameter was tested. The results are as follows.
[0222] Table 1 Antibacterial ability test of antibacterial materials against Staphylococcus aureus
[0223]
[0224] Table 2 Antibacterial ability test of antibacterial materials against Escherichia coli
[0225]
[0226] It can be seen from the data that the silver-containing nanofiber membrane prepared by electrostatic coating has obvious antibacterial effect on Staphylococcus aureus and Escherichia coli.
[0227] Experiment 9:
[0228] Dissolve 0.2-3 parts of povidone iodine and 5-15 parts of polyurethane in an electrocoating solution of 80-100 parts of N,N-dimethylformamide and 10-30 parts of hexafluoroisopropanol, stir at room temperature for 12-14 hours, and mix well to obtain an antibacterial solution.
[0229] An antibacterial solution is used to electrostatically coat the substrate 500, and the electrostatic coating process parameters are: the electrostatic coating applied voltage is 5-50KV, the receiving distance is 5-45cm, the spinning temperature is 10-15°C, the environmental relative humidity is 30-45%, the drum speed is 20-250rpm, and the fiber membrane carrier is cotton yarn to obtain antibacterial cotton yarn.
[0230] The agar plate diffusion method was used to test the antibacterial effect of cotton yarn with antibacterial materials (Group A) and without antibacterial materials (Group B) on Staphylococcus aureus and Escherichia coli and test the diameter of the antibacterial ring. Weigh 3.6NB nutrient powder, add 200ml deionized water, heat to dissolve, adjust the pH value to 7.2-7.4, sterilize at 115℃ for 30min, and incubate in a 37℃ incubator overnight to obtain the test strains. The discs (1cm) of different fiber samples were placed on the solidified agar gel of different culture dishes and incubated at 37℃ for 48h.
[0231] Table 1 Antibacterial ability test of antibacterial materials against Escherichia coli
[0232]
[0233] Table 2 Antibacterial ability test of antibacterial materials against Staphylococcus aureus
[0234]
[0235] The results showed that after adding antibacterial material fibers, the test cotton yarn produced significant antibacterial rings against Staphylococcus aureus and Escherichia coli, with the widths of the antibacterial bands reaching 8mm and 10mm respectively, with good antibacterial effects, while cotton yarn without added antibacterial materials did not produce antibacterial rings.
[0236] Experiment 10:
[0237] 0.5-2 parts of silver nitrate solution and 5-11 parts of polyacrylonitrile are dissolved in 100 parts of N,N-dimethylformamide, stirred at room temperature for 16 hours, and mixed evenly to obtain an antibacterial solution.
[0238] The electrostatic coating process parameters are: voltage 5-35 kV, ambient temperature 18-25° C., ambient relative humidity 30%-40%, and roller speed 20-200 rpm.
[0239] Experiment 11:
[0240] 1 to 3 parts of graphene solution loaded with silver nanoparticles and 8 to 18 parts of polyurethane are dissolved in 100 parts of N,N-dimethylformamide, stirred at room temperature for 12 hours, and mixed evenly to obtain an antibacterial liquid.
[0241] The electrostatic coating process parameters are: voltage 10-40 kV, ambient temperature 18-25° C., ambient relative humidity 30%-45%, and drum speed 30-200 rpm.
[0242] Experiment 12:
[0243] 0.2-3 parts of povidone-iodine solution and 6-13 parts of polyacrylonitrile are dissolved in 100 parts of N,N-dimethylformamide, stirred at room temperature for 12 hours, and mixed evenly to obtain an antibacterial solution.
[0244] The electrostatic coating process parameters are: voltage 10-40 kV, ambient temperature 18-25° C., ambient relative humidity 30%-45%, and roller speed 25-150 rpm.
[0245] Experiment 13:
[0246] 1-5 parts of carbon-60 solution loaded with lavender essential oil and 6-13 parts of polyacrylonitrile are dissolved in an electrocoating solution of 80-90 parts of N,N-dimethylformamide and 10-20 parts of hexafluoroisopropanol, stirred at room temperature for 16 hours, and mixed evenly to obtain an antibacterial solution.
[0247] The electrostatic coating process parameters are: voltage 10-40 kV, ambient temperature 18-25° C., ambient relative humidity 30%-45%, and roller speed 25-150 rpm.
[0248] Experiment 14:
[0249] 0.05-2 parts of zinc oxide and 8-16 parts of polyurethane are dissolved in 100 parts of N,N-dimethylformamide, stirred at room temperature for 12 hours, and mixed evenly to obtain an antibacterial liquid.
[0250] The electrostatic coating process parameters are: voltage 10-40 kV, ambient temperature 18-25° C., ambient relative humidity 30%-45%, and roller speed 25-150 rpm.
[0251] Example 3
[0252] This embodiment is a further improvement on Embodiment 1, and the repeated contents will not be repeated here.
[0253] The present invention relates to a method for preparing a functional blended yarn, which comprises the following steps:
[0254] Nano-scale materials with antibacterial, deodorizing, and mite-inhibiting properties are made from soluble polymer electrocoating liquid mixed with additives;
[0255] Adjusting the spacing and / or potential difference required for coating based on the type and / or ratio of polymers and additives mixed in the nanoscale material;
[0256] The natural fibers without antibacterial, deodorizing, and mite-inhibiting functions are spread out to form a first fiber membrane, and the chemical fiber materials of nanoscale materials are added to the first fiber membrane by electrostatic coating to form a second fiber membrane. The mass content of natural fiber materials in the nanoscale functional chemical fibers is not less than 90%, making the performance of the composite yarn close to that of natural fiber yarn to a great extent.
[0257] The nanoscale functional chemical fibers used in electrostatic coating contain no less than 90% nanoscale materials, which are materials with a maximum diameter of the smallest cross section of less than 1 micron. This avoids uneven dyeing of the composite yarn or fabric produced. Due to the high specific surface area of nanomaterials, they can form a strong riveting effect with natural fibers and are not easy to fall off during washing, rubbing, etc. In addition, due to the high surface activity of nanoscale materials, the composite yarn or fabric produced by this method exhibits good antibacterial, antibacterial, and anti-mite properties.
[0258] The quality of the second fiber membrane is verified, and the preset potential difference and / or spacing is adjusted based on the verification result.
[0259] The present invention also provides a method for uniformly distributing and tightly fixing nanomaterials on natural fibers, the method comprising the following steps:
[0260] The natural fiber is spread out after combing to form a sufficiently thin film, namely the first fiber film. The first fiber film is flattened at the receiving end 120 and is tightly attached to the receiving end 120 without falling off. The first fiber film passes through the electrostatic coating device 100, and the electrostatic coating device 100 attaches the nanoscale material to the first fiber film through a high voltage electric field; the mixture mixed with a soluble polymer and an additive is stirred to form an electrocoating liquid; the spacing and / or potential difference required for coating are adjusted based on the type and / or proportion of the polymer and additive mixed in the electrocoating liquid, and the electrocoating liquid is electrostatically coated on the substrate 500 as the first fiber film to form a second fiber film by electrostatic coating; the quality of the second fiber film is checked, and the pre-set potential difference and / or spacing is adjusted based on the check result. By spreading the natural fiber into a thin film as the substrate 500, and using the electrostatic coating device 100 to accurately attach the nanomaterial to the natural fiber film under a high voltage electric field, the method achieves uniform distribution of the nanomaterial and close integration with the natural fiber. The parameter settings in the electrostatic coating process were optimized by finely adjusting the types and proportions of polymers and additives in the electrocoating solution.
Claims
1. A functional blended yarn, characterized in that: The fibers of the blended yarn include natural fibers and nano-scale functional chemical fibers, wherein: The electrocoating liquid related to the chemical fiber is attached to the first fiber membrane formed by the natural fiber in an electrostatic coating manner to form a second fiber membrane of mixed natural fiber and chemical fiber. During the electrostatic coating process, the high molecular polymer in the electrocoating liquid forms a wettability fixation on the natural fiber, so that the high molecular polymer is embedded in the natural fiber to enhance the functionality of the natural fiber. The blended yarn is produced by spinning the second fiber membrane.
2. The blended yarn according to claim 1, characterized in that: The electrostatic coating method includes: The electro-coating liquid forms nano-scale fibers, short rods or particles under the action of a high voltage electric field and is coated on the surface of the first fiber membrane.
3. The blended yarn according to claim 1 or 2, characterized in that: In the case where the electrocoating liquid is formed by mixing at least three substances, the mixing method of the electrocoating liquid includes: The electrocoating liquid provided by at least two liquid storage boxes (144) is mixed during the liquid supply process; The electrocoating liquid provided by at least two liquid storage boxes (144) is immediately contacted and sprayed out when the liquid is discharged; The electrocoating liquid provided by at least two liquid storage boxes (144) forms a core-sheath structure in which the sheath liquid surrounds the core liquid when sprayed.
4. The blended yarn according to any one of claims 1 to 3, characterized in that: The electrostatic coating process of the second fiber membrane includes: In the case where the voltage of the high voltage electric field is unstable, the electrocoating jet of the electrocoating liquid is uneven and forms a bead string structure. The short rods in the bead string structure wrap the first fiber membrane in a liquid state and are riveted in the first fiber membrane.
5. The blended yarn according to any one of claims 1 to 4, characterized in that: The mass content of natural fiber material in the blended yarn is not less than 90%; Alternatively, the proportion of nanoscale materials in the nanoscale functional chemical fibers is not less than 90%.
6. A method for preparing a functional blended yarn, characterized in that: The method comprises: forming a first fiber membrane from natural fibers; The electrocoating liquid related to chemical fibers is attached to the first fiber membrane by electrostatic coating to form a second fiber membrane of mixed natural fibers and chemical fibers. During the electrostatic coating process, the high molecular polymer in the electrocoating liquid forms a wettability fixation on the natural fibers, so that the high molecular polymer is embedded in the natural fibers to enhance the functionality of the natural fibers. The second fiber membrane is made into the blended yarn.
7. The method according to claim 6, characterized in that The method further comprises: The potential difference, voltage and variation rule of the high voltage electric field are adjusted so that the electrocoating liquid forms nanometer-scale fibers, short rods or particles under the action of the high voltage electric field and is coated on the surface of the first fiber membrane.
8. The method according to claim 6 or 7, characterized in that: In the case where the electrocoating liquid is formed by mixing at least three substances, the mixing method of the electrocoating liquid includes: The electrocoating liquid provided by at least two liquid storage boxes (144) is mixed during the liquid supply process; The electrocoating liquid provided by at least two liquid storage boxes (144) is immediately contacted and sprayed out when the liquid is discharged; The electrocoating liquid provided by at least two liquid storage boxes (144) forms a core-sheath structure in which the sheath liquid surrounds the core liquid when sprayed.
9. The method according to any one of claims 6 to 8, characterized in that: The method further comprises: The voltage of the high voltage electric field is adjusted to an unstable state so that the electrocoating jet of the electrocoating liquid is uneven and forms a bead string structure, The short rods in the bead string structure wrap the first fiber membrane in a liquid state and are riveted in the first fiber membrane.
10. The method according to any one of claims 6 to 9, characterized in that: The method further comprises: The electric field strength of the high voltage electric field is adjusted to an unstable state so that the electrocoating jet of the electrocoating liquid is uneven and forms droplets, The liquid droplets are deposited on the surface and / or inside of the first fiber membrane, and are solidified into particles on the surface and / or inside of the first fiber membrane to achieve riveting.
Citation Information
Patent Citations
Method for preparing nano-fiber blending composite yarn
CN103572448A
Uniform distribution device and method of nanofibers in blended yarn system
CN107938083A
Method for preparing non-ironing multifunctional blended yarn by utilizing electrostatic spinning nanotechnology
CN112553734A
Composite yarn with antibacterial and antistatic functions and preparation method and application thereof
CN114737266A